Increased Meningeal T and Plasma Cell Infiltration is Associated with Early Subpial Cortical Demyelination in Common Marmosets with Experimental Autoimmune Encephalomyelitis. (12th September 2014) - Kramann, Nadine; Neid, Katharina; Menken, Lena; Schlumbohm, Christina; Stadelmann, Christine; Fuchs, Eberhard; Brück, Wolfgang; Wegner, Christiane
Abstract: Subpial cortical demyelination (SCD) accounts for the greatest proportion of demyelinated cortex in multiple sclerosis (MS). SCD is already found in biopsy cases with early MS and in marmosets with experimental autoimmune encephalomyelitis (EAE), but the pathogenesis of SCD is not well understood. The objective of this study was to investigate whether and, if so, which meningeal inflammatory cells were associated with early SCD in marmosets with EAE. Immunohistochemistry was performed to analyze brain samples from eight control animals and eight marmosets immunized with myelin oligodendrocyte glycoprotein. Meningeal T, B and plasma cells were quantified adjacent to SCD, normal‐appearing EAE cortex (NAC) and control marmoset cortex. SCD areas appeared mostly hypocellular with low‐grade microglial activation. In marmosets with EAE, meninges adjacent to SCD showed significantly increased T cells paralleled by elevated plasma cells, but unaltered B cell numbers compared with NAC. The elevation of meningeal T and plasma cells was a specific finding topographically associated with SCD, as the meninges overlying NAC displayed similarly low T, B and plasma cell numbers as control cortex. These findings suggest that local meningeal T and plasma cell infiltration contributes to the pathogenesis of SCD in marmosets with EAE.